(untitled) - Blundell, Barry (Hoboken, N.J., 2007)
This book builds on a previous work (‘Creative 3-D Display and Interaction Interfaces’) but may be read as a stand-alone book. A trans-disciplinary approach is adopted thereby making the content accessible to wide-ranging audiences from both the sciences and humanities. Additionally, the book is highly relevant to computer users who would like to learn more about new approaches to computer interaction, to those wishing to develop new forms of creative digital media and to those within industry who are involved in the advancement of computers and computer related products
Keywords: Computer graphics,Three-dimensional imaging,Đồ họa máy tính,Hình không gian 3 chiều